Post-debridement morphology of root canals of maxillary incisors A study using injectable silicone - Ramirez, Ma. Rosario A.; Suarez, Ma. Victoria H.; Dominguez, Liza (Adviser).
Sixty-five freshly extracted maxillary incisors with fully formed, patient apical foramens were filed and reamed using the step-back technique. An injectable silicone impression material was introduced into the prepared root canals, after which the teeth were decalcified. The silicone models were then studied under a dissecting microscope, after which each model was sectioned 1 mm. and 2 mm. from the apex. Each section was then studied under a compound microscope with a micrometer eyepiece. Many irregularities, fins, instrument markings were observed in the silicone models. Many of the sectioned portions were oval, and only a few approached the ideal round configuration.
Seminar Paper--Doctor of Dental Medicine--University of the Philippines Manila.
Keywords: Endodontics